Thalidomide in newly diagnosed multiple myeloma: influence of thalidomide treatment on peripheral blood stem cell collection yield - Breitkreutz, Iris; Lokhorst, H. M.; Raab, Marc-Steffen; Holt, B. van der; Cremer, Friedrich Walter; Herrmann, Dieter; Glasmacher, A.; Schmidt-Wolf, I. G. H.; Blau, I. W.; Martin, H.; Salwender, H.; Haenel, A.; et al. (Leukemia, 2007)
In a phase III randomized, multicenter study, the German-speaking Myeloma-Multicenter Group (GMMG) and the Dutch-Belgian Hemato-Oncology Cooperative Group (HOVON) group investigated the influence of thalidomide (Thal) on the outcome of peripheral blood stem cell (PBSC) collection in multiple myeloma (MM) before peripheral autologous blood stem cell transplantation (ABSCT). We analyzed the data of 398 myeloma patients after induction with Thal, doxorubicin and dexamethasone (TAD) in comparison with vincristine, doxorubicin and dexamethasone (VAD) followed by mobilization with cyclophosphamide, doxorubicin, dexamethasone (CAD) and PBSC collection. Within both the study groups, patients treated with TAD showed to collect significantly fewer CD34+ cells compared with VAD (GMMG, TAD: median 9.8 × 106/kg; range 2.0-33.6; VAD: median 10.9 × 106/kg range 3.0-36.0; P=0.02) (HOVON, TAD: median 7.4 × 106/kg; range 2.0-33.0; VAD: median 9.4 × 106/kg; range 0.0-48.7; P=0.009). However, engraftment after peripheral autologous stem cell transplantation showed no difference between Thal and VAD groups. We conclude that Thal as a part of induction regimen is associated with better response rates (GMMG-HD3: CR/PR 79%, VAD: CR/PR 58%; HOVON-50: TAD: CR/PR 81%, VAD: CR/PR 61%), but significantly affects the yield of PBSC collection. Nevertheless, the number of total CD34+ cells collected was sufficient for double autologous transplantation in 82% of the Thal patients, with at least 2.5 × 106/kg CD34+ cells.
Gesehen am 11.02.2022